2015
DOI: 10.5271/sjweh.3491
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial work environment and risk of ischemic stroke and coronary heart disease: a prospective longitudinal study of 75 236 construction workers

Abstract: Psychosocial work environment and risk of ischemic stroke and coronary heart disease: a prospective longitudinal study of 75 236 construction workers by Schiöler L, Söderberg M, Rosengren A, Järvholm B, Torén K Ischemic stroke and coronary heart disease are common and costly for society, and hence knowledge about modifiable risk factors is important. This study of a large cohort of relatively young and socially homogenous construction workers contributes to the knowledge regarding the association with the psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The presence of chronic toxic stress from which an individual is unable to adapt to or overcome contributes to the cumulative physiological dysregulation and ultimate decline of multiple physiological systems including cardiovascular function, glucose regulation, and neurological functions [98,99]. Chronic stress is a major risk factor for the development of hypertension [100] and related cardiovascular disease [101,102]. With regard to blood pressure, both acute and chronic stress are known to activate the sympathetic nervous system to release norepinephrine from sympathetic nerve terminal that cause vasoconstriction and activate the hypothalamicpituitary-adrenal axis (HPA).…”
Section: Chronic Stress: Common Mechanisms In Hypertension and Brain mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of chronic toxic stress from which an individual is unable to adapt to or overcome contributes to the cumulative physiological dysregulation and ultimate decline of multiple physiological systems including cardiovascular function, glucose regulation, and neurological functions [98,99]. Chronic stress is a major risk factor for the development of hypertension [100] and related cardiovascular disease [101,102]. With regard to blood pressure, both acute and chronic stress are known to activate the sympathetic nervous system to release norepinephrine from sympathetic nerve terminal that cause vasoconstriction and activate the hypothalamicpituitary-adrenal axis (HPA).…”
Section: Chronic Stress: Common Mechanisms In Hypertension and Brain mentioning
confidence: 99%
“…Chronic stress is a major risk factor for the development of hypertension [ 100 ] and related cardiovascular disease [ 101 , 102 ]. With regard to blood pressure, both acute and chronic stress are known to activate the sympathetic nervous system to release norepinephrine from sympathetic nerve terminal that cause vasoconstriction and activate the hypothalamic-pituitary-adrenal axis (HPA).…”
Section: Introductionmentioning
confidence: 99%
“…Although most studies contained proportions of men and women between 40% to 60% 6,11,12, , eight cohort studies focused exclusively on men or women [42][43][44][45][46][47][48][49] . The cohort sizes ranged from 25 to 4718 participants 20,50 , while the case-control studies ranged in size from 346 to 26,949 41,51 .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Retirement means removal of heavy work tasks and increased time for health promotion, but also introduces new stressors due to reduced income and loss of a social context, which, especially if leaving work involuntarily, is linked to depression and anxiety [8, 10]. A study based on a subsample of the cohort used in this paper [23] showed that most subjects reported low job demands and a supportive social climate. If these conditions can be generalized to the whole cohort, leaving work may have little or negative effects on mental health.…”
Section: Discussionmentioning
confidence: 99%